A method to identify investigative blind spots (MIBS): Addressing blunt-end factors of ultra-safe organizations’ investigation-work-as-done - Lundberg, Jonas; Woltjer, Rogier; Josefsson, Billy (Safety science, 2022)
•The paper presents a method to identify and address investigative blind spots (MIBS).•Blind spots are issues that are systematically not addressed in investigative work.•They emerge due to work pressures when using methods, or due to gaps in methods.•They can emerge in ultra-safe organizations with modern investigation methods.•The paper discusses and compares three cases of using the method at an air navigation provider. Ultra-safe organizations, such as Air Navigation Service Providers (ANSPs), have extensive safety management organizations and generally excellent safety records with very few serious incidents and accidents. This development has been supported by increasingly advanced and effective methods. However, recent research has uncovered how the application of even advanced incident investigation methods is subject to the same pressures of the reality of everyday work, similar to other safety-critical work tasks. They may therefore also have “incidents”, where all issues are not examined with desired thoroughness, and all recommendations are not formulated or implemented with desired effectiveness. This development may be driven by different factors. For instance, the economic pressure on ANSPs is arguably high in Europe’s competitive aviation market. This speaks for an efficient and pragmatic method for investigating organizational factors affecting incident investigation work. The foundation for such a method existed in prior research, in the form of lists of risk factors for investigative work. In this paper, we present the Method for identifying Investigative Blind Spots (MIBS). We also describe, compare, and assess its development and application, at a Swedish ANSP. Incident investigators were involved in a series of semi-structured workshops to identify possible “blind spots” in their own investigation practices (investigation-work-as-done), i.e. organizational factors that impede or otherwise affect the various phases of the investigative process (investigation-work-as-imagined). This resulted in a method description with an associated set of discussion cards that ultra-safe organizations can use to address blunt-end factors of their investigation-work-as-done.